2020
DOI: 10.1111/apt.15643
|View full text |Cite
|
Sign up to set email alerts
|

Review article: determination of the therapeutic range for therapeutic drug monitoring of adalimumab and infliximab in patients with inflammatory bowel disease

Abstract: Background Clinical application of therapeutic drug monitoring (TDM) to optimise anti‐TNF therapies in patients with IBD depends upon target ranges. Aims To review methodology used to determine therapeutic ranges and critically compare and contrast its application to infliximab and adalimumab. Methods A systematic review was performed, and relevant literature was summarised and critically examined. Results Upper limits of the therapeutic range are determined by toxicity, a plateau response and cost. Lower limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 91 publications
5
50
0
Order By: Relevance
“…A previous study on trough level of ADA during maintenance therapy reported that 5-5.8 and 4.9-7.1 µg/mL were the lower limits of the therapeutic range when clinical remission and mucosal healing were the desired targets, respectively; both limits are approximately 4 µg/mL lower than our non-trough level. As these are the lower limits of the therapeutic range and the variation in the levels over 2 weeks between successive ADA administrations is approximately 3 µg/mL [16], our results are valid.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…A previous study on trough level of ADA during maintenance therapy reported that 5-5.8 and 4.9-7.1 µg/mL were the lower limits of the therapeutic range when clinical remission and mucosal healing were the desired targets, respectively; both limits are approximately 4 µg/mL lower than our non-trough level. As these are the lower limits of the therapeutic range and the variation in the levels over 2 weeks between successive ADA administrations is approximately 3 µg/mL [16], our results are valid.…”
Section: Discussionsupporting
confidence: 68%
“…Interestingly, Ward et al reported that the trough level could be estimated from serum ADA level from days 3 to 9 after ADA injection, suggesting the feasibility of TDM even without trough level measurement of ADA [15]. In addition, authors reported that 8 weeks after the initiation of ADA therapy, the average uctuation in ADA level during the 2 weeks between successive administrations of ADA was approximately 3 µg/mL [16]. Therefore, the purpose of our study was to analyze the effects of serum ADA levels, including its nontrough levels, and AAA presence on subsequent treatment outcomes in patients with IBD receiving ADA.…”
Section: Introductionmentioning
confidence: 99%
“…This was not influenced by changes in albumin, CRP, BMI or concomitant thiopurine. The effect of a 4‐5 µg/mL increase in levels is unknown, but is unlikely to be associated with adverse effects 20 . While the direction of change seems similar, the more than two‐fold greater increase in maternal infliximab levels found in the previous study compared with that in the current cohort may have reflected the lower numbers of observations in the earlier report.…”
Section: Discussionmentioning
confidence: 51%
“…As the therapeutic threshold for IFX is not well defined, we included simulations of PK targets of 3-5 mg/mL. [25][26][27] This study Table 3. Pharmacokinetic (PK) model simulations of attainment of PK targets of trough infliximab (IFX) concentrations of >3 mg/mL, >4 mg/mL, or >5 mg/mL for anti-IFX antibody negative (ADA-) or positive (ADAþ) patients in case of safety pausing IFX therapy in the entire third trimester of pregnancy (IFX-stop); continuation of steady IFX maintenance therapy in the third trimester of pregnancy (IFX cont.…”
Section: Discussionmentioning
confidence: 99%